The creative advantages of schizophrenia : the muse and the mad hatter - Kiritsis, Paul (Cambridge Scholars Publishing, 2019)
The aphorism that madness and creative genius are opposing sides of the same coin predates contemporary psychiatry and has existed since the time of the great Stagirite Aristotle. Schizophrenia is one mental disorder intimately linked with creative thinking and achievement. There is no shortage of eminent scientists, thinkers, writers, artists, composers, and political activists tentatively theorized to have precariously balanced the great divide between the demons of schizophrenia and the muses of creative illumination, including Rene Descartes, Emanuel Swedenborg, John Forbes Nash, Leonardo.